Alejandra Pizarnik and the non-place of poetic bodies, delirium and creative drive (2022)
The intimacy of Alejandra Pizarnik, weaver of words of torment and madness, gives a glimpse of the irrational and musical hells that traverse a particular expression of poetic psyche: the word that dares to speak a night that presages elegy. The wounded word and the fatally broken life of this author place the reader in a permanent dialogue between vitalism and existentialism. The purpose of this article is to reflect on the limits of the human will and the relationship between life and literary work, based on a dissertation on the texts of Pizarnik, who, rather than striving to embellish resignation, prefers to inquire about the destiny and meaning of the poetic word, caged and incapable of expressing the wounds of being. She searches, from precise rhetorical figures of unquestionable sensorial impact, for the place of poetic bodies in the intricacies of a maladjusted existence without compass. An existence that is a mirror (or perhaps an abyss) of the reality unveiled by a philosophical poetry in search of impossible meaning and desire, but whose search remains a necessary topic of literature.